2002
DOI: 10.1073/pnas.212515299
|View full text |Cite
|
Sign up to set email alerts
|

Soluble peptide–MHC monomers cause activation of CD8+T cells through transfer of the peptide to T cell MHC molecules

Abstract: T cell receptor (TCR)-mediated activation of CD4 ؉ T cells is known to require multivalent engagement of the TCR by, for example, oligomeric peptide-MHC complexes. In contrast, for CD8 ؉ T cells, there is evidence for TCR-mediated activation by univalent engagement of the TCR. We have here compared oligomeric and monomeric L d and K b peptide-MHC complexes and free peptide as stimulators of CD8 ؉ T cells expressing the 2C TCR. We found that the monomers are indeed effective in activating naïve and effector CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
60
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 40 publications
4
60
1
1
Order By: Relevance
“…Thus, CTL acquire covalent pepMHC complexes in a signallingdependent manner. This observation also rules out the possibility that fluorescent peptide transfer results from peptide dissociation followed by reassociation on the MHC molecules of the CTL, a process that was proposed to account for CTL activation by soluble pepMHC monomers [41,42]. Detectable acquisition of covalent pepMHC complexes and IFN-c production require higher levels of TCR engagement than does triggering of biotin capture or cytotoxicity…”
Section: Ctl Capture Covalent Pepmhc Complexesmentioning
confidence: 79%
“…Thus, CTL acquire covalent pepMHC complexes in a signallingdependent manner. This observation also rules out the possibility that fluorescent peptide transfer results from peptide dissociation followed by reassociation on the MHC molecules of the CTL, a process that was proposed to account for CTL activation by soluble pepMHC monomers [41,42]. Detectable acquisition of covalent pepMHC complexes and IFN-c production require higher levels of TCR engagement than does triggering of biotin capture or cytotoxicity…”
Section: Ctl Capture Covalent Pepmhc Complexesmentioning
confidence: 79%
“…Cross-presentation is a major pathway by which DNA vaccines elicit T cell responses, but the inefficiency of cross-presentation can be a contributing factor to relatively weak T cell responses after DNA vaccination. In addition, recent studies have documented the cross-presentation of synthetic peptides from recombinant MHC-I tetramers used to activate T cells (22,23). Thus biochemical stability of the SCT is a requirement for improved DNA vaccination or MHC-I tetramer approaches.…”
mentioning
confidence: 99%
“…This type of study in CD4 T cells showed that dimers and higher oligomers of cognate class II MHC-peptide complexes were able to stimulate many T cell markers such as TCR down-regulation (4), CD69 up-regulation (5), and CD25 up-regulation (6); conversely, monomeric MHC-peptide complexes were not able to induce such markers (7)(8)(9)(10). When similar studies have been undertaken treating CD8 T cells with soluble, recombinant class I MHC-peptide complexes, conflicting studies reported activation in response to oligomeric complexes (10 -15), to monomeric complexes (13)(14)(15), and even to free peptide (14,15). A partial explanation for this discrepancy may be "cross-presentation" of peptide by T cells, wherein peptide adventitiously released from soluble MHC monomers can be loaded onto T cell endogenous class I MHC molecules with resultant T-T presentation and activation (14,15).…”
mentioning
confidence: 99%
“…When similar studies have been undertaken treating CD8 T cells with soluble, recombinant class I MHC-peptide complexes, conflicting studies reported activation in response to oligomeric complexes (10 -15), to monomeric complexes (13)(14)(15), and even to free peptide (14,15). A partial explanation for this discrepancy may be "cross-presentation" of peptide by T cells, wherein peptide adventitiously released from soluble MHC monomers can be loaded onto T cell endogenous class I MHC molecules with resultant T-T presentation and activation (14,15). When T cells that do not express endogenous MHC are used, neither peptide nor class I MHC monomers caused down-regulation of TCR or up-regulation of activation markers (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation